Diagnóstico/resultados e intervenções de enfermagem da CIPE® para a pessoa idosa institucionalizada - Oliveira, Jullyana Marion Medeiros de (2014)
The process of demographic aging has led to the raise of necessity for a specialized care developed by Institutions of Long Stay for Elders. However, it has been perceived that this support network in expansion is disarticulated with the networks of health attention, once the health actions are performed in its majority by the heath team of the institution, being the nursing professionals the responsible ones for developing such care. Notwithstanding, the nursing care in these homes is being performed, in its majority, without a systematization of assistance compromising the resoluteness and the goal aimed by the actions of the care. Objective: to identify the focuses of nursing practice in the health evaluation of the elder institutionalized person, to build headings diagnosis/ results of ICNP® to the elder institutionalized person and to make Interventions of Nursing, using the ICNP®, from the headings diagnosis/ results validated to the institutionalized elder person. Methodology: It was made through a methodological research, developed at an Institution of Long Stay for Elders in the city of Natal/RN, with participation of 83 elder persons resident in the institution, using the theoretical referential of the Human Basic Needs Theory by Wanda Horta and the technic of cross-mapping and the validation of contents by specialists. For its execution five steps were taken: I) Identification of the nursing practice focuses; II) Making of the headings of diagnosis/ results of nursing; III) Cross-mapping of the concepts built with the ICNP® 2013 version; IV) Validation of the contents by specialists of the headings diagnosis/ results of nursing; and V) Making of the headings of interventions of nursing for validated diagnosis. The research has been appreciated by the Ethics Committee from the Center of Health Sciences from Federal University of Paraíba, Brazilian platform, respecting the standardization of Resolution N 466/2012 from the National Counsel of Health, referring to ethical aspects of research involving human beings. The study has been approved under the protocol N 081/14 and CAEE 27593814.1.0000.5188. Results: 192 focuses of nursing practice were found, 113 in psychobiological needs, 74 in the psychosocial needs and 5 in the psychospiritual needs, which allowed the construction of 129 headings of diagnostics / results of nursing, that were submitted to a cross-mapping process in correspondence with the concepts of ICNP® Version 2013 resulting in 60 constant headings and 69 not constant in this validation. In the validation of content phase 72 diagnosis / results of nursing were validated, to which were built 383 headings of nursing intervention. Conclusion: It has been accomplished the hypothesis that there are focuses of the nursing practice which are identified in the health evaluation of the elder persons resident in ILPI and which also allow the making of headings of diagnosis/results, and nursing intervention, using the ICNP®. It is hoped that the proposal of a systematized nursing care, through the use of heading of diagnosis/results and the intervention of nursing, may be able to subside and build the scientificism of the technological know-how as well as the Nursing professional autonomy to the institutionalized elder person.